Monte Carlo simulation investigation on the minitype reference radiation employed for the calibration of gamma ray dose or dose rate meters. (15th February 2018) - Li, Wenjie; Liu, Yixin; Wei, Biao; Feng, Peng; Xu, Yang; Mao, Benjiang
Abstract: Minitype reference radiation (MRR) based on a cesium-137 (Cs-137) isotope radioactive source is a core component for carrying out field calibration on gamma ray dose or dose rate meters. To explore the source of scattering rays in the MRR, and their influence on dose field distribution, we calculated the radiation field of the MRR with different shielding wall materials, different sizes of shielding boxes, and different detectors. The investigation results provide theoretical and technical support for better understanding the MRR, and for developing field calibration technologies.